The Volitionist'sManifesto - Hyman, Michael R. (Journal of business ethics, 2000)
Many popular business strategies, such as re-engineering, core competency, and value engineering, may achieve short-term profits by antagonizing workers and alienating customers. We contend that self-actualized companies must create an ethical business environment grounded in three ethical principles. To suggest these principles, which characterize all "volitionist companies", we first review two typical problems and the questionable ways that some companies resolved them. Then, we discuss these principles and compare "volitionism" to three well- known normative ethical theories. Finally, we show that these principles form the core of at least four popular management theories.